2005
DOI: 10.1021/bi050494i
|View full text |Cite
|
Sign up to set email alerts
|

Araneoid Egg Case Silk:  A Fibroin with Novel Ensemble Repeat Units from the Black Widow Spider, Latrodectus hesperus

Abstract: Araneoid spiders use specialized abdominal glands to manufacture up to seven different protein-based silks/glues that have diverse physical properties. The fibroin sequences that encode egg case fibers (cover silk for the egg case sac) and the secondary structure of these threads have not been previously determined. In this study, MALDI tandem TOF mass spectrometry (MS/MS) and reverse genetics were used to isolate the first egg case fibroin, named tubuliform spidroin 1 (TuSp1), from the black widow spider, Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 30 publications
3
80
0
Order By: Relevance
“…The silk classes of a typical 'gluey silk' orb-weaver (Araneoidea) female include (i) major ampullate silk, which exhibits great tensile strength and is employed in draglines, bridgelines, and web radii 11,12 ; (ii) minor ampullate silk, used for inelastic temporary spirals during web building 11,12 ; (iii) cement-like piriform silk that bonds fibers together and to other substrates 13,14 ; (iv) strong, yet flexible aciniform silk used for prey wrapping and egg case insulation 15 ; (v) tubuliform and cylindriform silk that constitutes the tough outer layer of egg cases 16,17 ; (vi) flagelliform silk that exhibits unparalleled extensibility and is used in the capture spiral 18,19 ; and (vii) the viscous and sticky aggregate silk that aids in prey capture [20][21][22][23][24] . Many spider species produce just a subset of these silk classes, and some produce yet other silk types, including cribellate silk 25 .…”
mentioning
confidence: 99%
“…The silk classes of a typical 'gluey silk' orb-weaver (Araneoidea) female include (i) major ampullate silk, which exhibits great tensile strength and is employed in draglines, bridgelines, and web radii 11,12 ; (ii) minor ampullate silk, used for inelastic temporary spirals during web building 11,12 ; (iii) cement-like piriform silk that bonds fibers together and to other substrates 13,14 ; (iv) strong, yet flexible aciniform silk used for prey wrapping and egg case insulation 15 ; (v) tubuliform and cylindriform silk that constitutes the tough outer layer of egg cases 16,17 ; (vi) flagelliform silk that exhibits unparalleled extensibility and is used in the capture spiral 18,19 ; and (vii) the viscous and sticky aggregate silk that aids in prey capture [20][21][22][23][24] . Many spider species produce just a subset of these silk classes, and some produce yet other silk types, including cribellate silk 25 .…”
mentioning
confidence: 99%
“…The presence of two different fiber types implies tubuliform and aciniform fibers provide a unique role that is central to the protection of spiderlings during development. Biochemical studies have shown that aciniform silks contain the fibroin AcSp1-like and the tubuliform silks contain at least three different proteins: TuSp1, ECP-1 and ECP-2 (Hu et al, 2005;2006b). Scanning electron microscopy, along with amino acid composition analyses performed on the egg sacs, support that tubuliform silks, based upon volume, constitute the bulk of egg sac fibers.…”
Section: Molecular Components Of Tubuliform Silksmentioning
confidence: 95%
“…Internal block repeats are ~184 amino acids in length and are extremely homogenous in nature. Short polyalanine stretches are highly iterated in the TuSp1 sequence and 13 C NMR spectroscopy demonstrates that the majority of alanine is in a betasheet structure in post-spun egg case silk (Hu et al, 2005). The ECPs (ECP-1 and ECP-2) are also components of tubuliform silks (Hu et al, 2006b).…”
Section: Molecular Components Of Tubuliform Silksmentioning
confidence: 99%
“…In itially the spider used to make a beam bridge between two supports and after then with the time they spin their web with the help of the excretion fro m their ampullatory gland [24].…”
Section: To Buil D Up Their Web They Follow Patternmentioning
confidence: 99%
“…[f] MA spidroins are stored in the lu men of the gland in the presence of sodium and chloride ions, and during fiber spinning these ions are exchanged for potassium and phosphate ions [23][24]. …”
Section: Spinning Of S Pi Der Silkmentioning
confidence: 99%